(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Skinner systematically published, from 1930 to 1990 and there are a few published listings of Skinner’s work. Various contexts and criteria were used by each author yielding to differences among the lists. The present listing of Skinner’s published work was based on eight previous ones and on other non-systematic information of Skinner published work. Books, articles, book reviews, abstracts, letters to editors, and interviews are listed. Information on republication, especially in Portuguese is also listed. The present list presents the references of 295 entries, of which the authors directly checked 269.